2008
DOI: 10.17221/2786-pse
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organic fertilizers application on phosphorus and potassium bioavailabilit

Abstract: A prerequisite to use organic fertilizers in a sustainable way is to quantify the amount of phosphorus and potassium available for plants that could be taken up by a crop. The objective of this study was to evaluate direct and subsequent influence of organic fertilizers addition (poultry manure and two types of composts) on the changes of bioavailability of phosphorus and potassium in soil and their accumulation in the aboveground oat biomass (Avena sativa L.) during three years. The available phosphorus and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Our results are also in agreement with Matula and Pechová (2007). Organic amendments increased the yields of oat as compared to mineral fertilizers (Hanč et al 2008). However, Ćustić et al (2003) observed no significant differences in yield after application of stable manure and mineral fertilizer to soil.…”
Section: Resultssupporting
confidence: 90%
“…Our results are also in agreement with Matula and Pechová (2007). Organic amendments increased the yields of oat as compared to mineral fertilizers (Hanč et al 2008). However, Ćustić et al (2003) observed no significant differences in yield after application of stable manure and mineral fertilizer to soil.…”
Section: Resultssupporting
confidence: 90%
“…Total Nutrient Content of the TPS A requirement to use organic amendments in a sustainable way is to quantify the amount of nutrients for plants that could be taken up by a crop [59]. Table 6 illustrates some of the main characteristics of the human compost (TPS) used to prepare the soil amendments before the addition of the biochars.…”
Section: Use Of Biochars Mixed With Compostmentioning
confidence: 99%
“…Apart from manure, slurry, sludge and other organic wastes (Hanč et al 2008, Kulhánek et al 2008, meat and bone meals (MBM) can be a viable alternative to phosphate fertilizers (Valenzuela et al 2001, Jeng et al 2006, Svoboda et al 2010, Chen et al 2011, Brod et al 2012, Nogalska et al 2012. Agricultural utilization of MBM has become an important consideration since a complete ban on the feeding of ruminant-derived protein to ruminants, which was introduced to control bovine spongiform encephalopathy (BSE).…”
mentioning
confidence: 99%